Carências e vulnerabilidades em metrópoles periféricas: análise comparativa entre Curitiba, Brasil e San Miguel de Tucumán, Argentina - Maurício Polidoro; Natalia Czytajlo; Marta Casares (Confins)
With the consolidation of an urban Latin America and the advancement of the metropolis, the debate on the implications of these processes is imperative in the urban agenda of the continent. Thus, understanding the dynamics, actors and spatial configurations of inequalities of multiscale shape and compared constitutes is an important advance in a theoretical and methodological point of view. In this sense, the paper attempts to propose, in the light of urbanization and metropolization processes of Brazil and Argentina, two indicators for Curitiba and San Miguel de Tucuman. The first, is guided to measure the supply of sanitation services and the second in demographics and education. Finally, we hope to contribute to a methodologically reading of spatial patterns between Latin American cities using census data.